The Influence of Transformational Leadership Style, Work Environment and Compensation on Employee Performance with Motivation as an Intervening Variable in PT Metindo Erasakti - Sugeng Suprapto; Safaria, Siti (Formosa Journal of Sustainable Research, 2024)
This quantitative research, 120 respondents with SmartPlS-4, aims to set a direct and indirect influence of the transformational leadership style on employee motivation and performance, work environment on employee motivation and performance, compensation on employee motivation and performance, motivation on employee performance, transformational leadership style, work environment and compensation on employee performance through work motivation as an intervening at PT Metindo Erasakti. transformational leadership do not impact performance, transformational leadership do not impact motivation. Compensation do not impact performance, compensation impact motivation, work environment impact performance. The work environment do not impact motivation. Motivation do not impact performance. Transformational leadership do not impact performance through motivation. Compensation do not impact performance through motivation. The work environment do not impact performance through motivation